2006
DOI: 10.1007/s10447-005-9005-y
|View full text |Cite
|
Sign up to set email alerts
|

Intergenerational Communication in Immigrant Punjabi Families: Implications for Helping Professionals

Abstract: This paper is an extension of the primary author's post-doctoral research on the Sikh diaspora in Vancouver, Canada. Drawing upon the orality, literacy and 'analytics' (critical inquiry) paradigm, the paper delineates the distinctive communication patterns that characterize each of three generations in the Punjabi community in that location. A sample intergenerational dialogue in the counselling context is provided to demonstrate the nature of fluidity in communication, and the implications for helping profess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…We adopted Harrell's (2000) definition of racial socialization, which refers to the degree to which Asian Indians are exposed to White racial and cultural contexts and the extent to which family socialization includes discussions of Indian cultural values and racism. Consistent with recent literature (Inman, 2006;Nayar & Sandhu, 2006), we defined first generation as those born and raised in India and migrated to the U.S. after age 18, and second generation as those either born and raised in the U.S., or migrated to the U.S. by age 18. Our delineation between first and second generations is based on literature which suggests a differing relationship between length of stay in the U.S. and identification with the mainstream culture or culture of origin (Deaux, 2004).…”
Section: Racism Related Stress Self-esteem and Coping: Moderating Rol...mentioning
confidence: 99%
“…We adopted Harrell's (2000) definition of racial socialization, which refers to the degree to which Asian Indians are exposed to White racial and cultural contexts and the extent to which family socialization includes discussions of Indian cultural values and racism. Consistent with recent literature (Inman, 2006;Nayar & Sandhu, 2006), we defined first generation as those born and raised in India and migrated to the U.S. after age 18, and second generation as those either born and raised in the U.S., or migrated to the U.S. by age 18. Our delineation between first and second generations is based on literature which suggests a differing relationship between length of stay in the U.S. and identification with the mainstream culture or culture of origin (Deaux, 2004).…”
Section: Racism Related Stress Self-esteem and Coping: Moderating Rol...mentioning
confidence: 99%
“…They concluded that there is variance in communication styles among first-, second-, and third-generational South Asians due to the level of acculturation (Thandi, Chahal & Cheema, 2005). This is echoed in Nayar and Sandhu's postdoctoral thesis exploring counseling nuances among the same community (Nayar & Sandhu, 2006). Elders, or immigrants who spent most of their lives in India before immigrating, usually have English as a learned language, and most of their knowledge is based on personal experiences.…”
Section: Degree Of Acculturationmentioning
confidence: 99%
“…Elders, or immigrants who spent most of their lives in India before immigrating, usually have English as a learned language, and most of their knowledge is based on personal experiences. Second and third generations are generally literate in English, and their knowledge is based on personal experiences and written language, as well as deductive reasoning and Western thought (Nayar & Sandhu, 2006;Thandi, Chahal & Cheema, 2005). Language also affects communication and access; Chang and colleagues' qualitative study of care providers' perspectives on treatment barriers for APIs suggests that a common language between staff and clients was needed to experience therapeutic nuances such as acceptance, connection, and openness.…”
Section: Degree Of Acculturationmentioning
confidence: 99%